2006
DOI: 10.1111/j.1365-2966.2006.10286.x
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency quasi-periodic oscillations from GRS 1915+105 in its C state

Abstract: We report the results of a systematic timing analysis of RXTE observations of GRS 1915+105 when the source was in its variability class θ, characterized by alternating soft and hard states on a time‐scale of a few hundred seconds. The aim was to examine the high‐frequency part of the power spectrum in order to confirm the hectohertz quasi‐periodic oscillations (QPO) previously reported from observations from mixed variability behaviours. During the hard intervals (corresponding to state C in the classification… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 25 publications
4
51
0
Order By: Relevance
“…Figure 13 shows the power-law tail of the observed flux for the HS and coronal emission. The simulation gives a photon index close to the one observed For GRS 1915+105 by Belloni et al (2006) in the SPL state. The phase-resolved energy spectra of the HS and the accretion disk are shown in Figure 14.…”
Section: Thermal Emissionsupporting
confidence: 75%
See 1 more Smart Citation
“…Figure 13 shows the power-law tail of the observed flux for the HS and coronal emission. The simulation gives a photon index close to the one observed For GRS 1915+105 by Belloni et al (2006) in the SPL state. The phase-resolved energy spectra of the HS and the accretion disk are shown in Figure 14.…”
Section: Thermal Emissionsupporting
confidence: 75%
“…The vertical optical depth of this layer is set to a constant, τ 0 =0.2, and the temperature of the hot electrons in the corona is set to T corona =30 keV. These parameters reproduce the observed photon index for GRS 1915+105 in the SPL state (Belloni et al 2006). The opening angle of the wedge is set to 2°.…”
Section: Corona Simulationmentioning
confidence: 99%
“…That the fourth state (the one with both LF and HF QPO) was observed in this source by Belloni et al (2006) is important as it gives support to and confidence in our tentative classification.…”
Section: Observations Of a State With Both Hf And Lf Qpossupporting
confidence: 63%
“…The main difference from the classification of Belloni et al (2000), based on GRS 1915+105, is that we separate their C state into two (AEI-dominated state and AEI-RWIdominated state), depending on the high frequency variability. Since this classification was first proposed, we have learned that HFQPOs occur in the C state as defined by Belloni et al (2000) (see Belloni et al 2006), so the AEI-MRI-dominated state has been observed in GRS 1915+105.…”
Section: A Model Independent Look At the Classificationmentioning
confidence: 99%
“…A high-frequency QPO was discovered in GRS 1915+105 during the θ class of variability by Belloni et al (2006); more recently Mikles et al (2009) showed that during the same class the color radius-frequency relation was different from the standard Keplerian one, and that the points were on the left side of the theoretical plot of Fig. 1.…”
Section: Grs 1915+105mentioning
confidence: 97%